2015
DOI: 10.1016/s1470-2045(14)71180-5
|View full text |Cite
|
Sign up to set email alerts
|

Transformation from non-small-cell lung cancer to small-cell lung cancer: molecular drivers and cells of origin

Abstract: Lung cancer is the most common cause of cancer deaths worldwide. The two broad histological subtypes of lung cancer are small-cell lung cancer (SCLC), which is the cause of 15% of cases, and non-small-cell lung cancer (NSCLC), which accounts for 85% of cases and includes adenocarcinoma, squamous-cell carcinoma, and large-cell carcinoma. Although NSCLC and SCLC are commonly thought to be different diseases owing to their distinct biology and genomic abnormalities, the idea that these malignant disorders might s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
715
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 734 publications
(736 citation statements)
references
References 64 publications
15
715
4
2
Order By: Relevance
“…As NSCLC typically grows and spreads more slowly compared with SCLC, it does not frequently respond to chemotherapy, in contrast to SCLC (10). Therefore, there are numerous efforts to develop NSCLC targeted chemotherapy based on oncogenic mutations, including those in epidermal growth factor receptor (EGFR) (10).…”
Section: Introductionmentioning
confidence: 99%
“…As NSCLC typically grows and spreads more slowly compared with SCLC, it does not frequently respond to chemotherapy, in contrast to SCLC (10). Therefore, there are numerous efforts to develop NSCLC targeted chemotherapy based on oncogenic mutations, including those in epidermal growth factor receptor (EGFR) (10).…”
Section: Introductionmentioning
confidence: 99%
“…It is currently indicated that combined-histology tumors and transformation occur more frequently in lung cancer types with EGFR-activating mutations compared with EGFR wild-type tumors. The reason for this may be that the cell of origin of certain EGFR-mutant adenocarcinomas, type II alveolar cells, also have the potential to become SCLC (17). Mixed EGFR-mutant NSCLC/SCLC histology has been reported in a number of cases, indicating a certain degree of dynamic plasticity between the two histologies in specific cases, without the selective pressure of the EGFR TKI (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Initially described in 2006, observations of small-cell lung cancer (sclc) transformation after egfr tki treatment represents a consistent acquired resistance mechanism, with a prevalence of 5% -14% in multiple case series 22 . The absence of response to egfr tkis is explained by decreased levels of egfr protein expression, a well-known feature of sclc [23][24][25] .…”
Section: Figurementioning
confidence: 99%